INEQUITY IN MATERNAL AND CHILD HEALTH CARE UTILISATION IN NIGERIA (2016)
The high maternal and child mortality rates of 500 per 100,000 and 128 per 1,000 live births are major research and health policy concerns often caused by inequity in utilisation of basic maternal and child healthcare in Nigeria. Although existing literature provided estimates of determinants of maternal and child healthcare utilisation, inequity in maternal and child healthcare utilisation has not been given adequate attention. This study, therefore, examined horizontal inequity in maternal and child health care utilisation in Nigeria. Social welfare and demand theories of healthcare utilisation were adopted. Concentration curves and standardised concentration index were used to analyse need variables (age and pregnancy status) and non-need variables (education and wealth) in the estimation of horizontal inequity in maternal and child health care utilisation. Maternal healthcare status was measured by antenatal attendance and delivery by skilled personnel, while child healthcare status was measured by immunisation experience and bednets usage. Two-part models (logit, negative binomial), logit and multinomial logit were used to estimate determinants of antenatal care, skilled delivery, immunisation and bednets utilisation, respectively. Data were derived from five sets of Nigeria Demographic and Health Survey (NDHS). The survey covered 8,781, 8,918, 2,572, 34,596 and 39,902 women aged 15-49 for 1990, 1999, 2003, 2008 and 2013, respectively. Data were analysed at p<0.05. The means were (0.7± 0.5), (0.1± 0.3), (0.7± 0.5) and (0.2±0.5) for antenatal care, skilled delivery, immunisation and bednets, respectively. Concentration curve for antenatal and skilled delivery revealed a positive horizontal inequity index of 0.26 to 0.37 and 0.32 to 0.48 from 1999 to 2013; indicating pro-rich inequity in utilisation with standardised concentration index of need variable subtotal of 0.001 to 0.002 and -0.03 to -0.02 and non-need variable subtotal of 0.26 to 0.37 and 0.19 to 0.30. Poorest women with no education had lower probability of attending antenatal care and utilising skilled delivery compared to richest women with higher education. This was evident in 2003 and 2013 when 56.8% and 25.0% of the poorest women and 39.4% and 39.5% of uneducated women were less likely to use antenatal and skilled delivery. Distance to health facility negatively influenced antenatal and skilled delivery utilisation. This was highest in 2003 with (β= -0.42 and -0.37). Child immunisation also exhibited positive horizontal inequity index of 0.22 to 0.07 from 1999 to 2013 indicating pro-rich inequity. In contrast bednets usage exhibited negative horizontal inequity index of -0.30 to -0.08 from 2003 to 2008, but turned positive at 0.13 in 2013, revealing pro-poor and pro-rich inequity. Children with poorest and uneducated mothers were less likely to be immunised and utilise treated bednets. This was more pronounced in 1999 to 2003 as 36.8% of children with poorest mothers and 41.3% of children with uneducated mothers were less likely to be immunised and more likely to use treated bednets in 2013. Education and wealth formed the basis of inequity in maternal and child healthcare utilisation in Nigeria. Empowerment programmes and improvement in education will enhance maternal and child healthcare utilisation by reducing mortality